Comparative diagnostic accuracy of pre-test clinical probability scores for the risk stratification of patients with suspected pulmonary embolism: a systematic review and Bayesian network meta-analysis - Ali Etemadi; Mohammadmobin Hosseini; Hamed Rafiee; Amir Mahboubi; Tara Mahmoodi; Toshiki Kuno; Yaser Jenab; Claire E. Raphael; Wilbert S. Aronow; Kaveh Hosseini; Jay Giri (BMC Pulmonary Medicine)
Abstract Background The primary evaluation of pulmonary embolism (PE) is complicated by the presence of various pre-test clinical probability scores (pCPS) with different cut-offs, all equally recommended by guidelines. This lack of consensus has led to practice variability, unnecessary imaging, and worse patient outcomes. We aim to provide more definitive insights through a holistic comparison of available pCPS. Methods PubMed, Embase and Web of Science, and Google Scholar were searched for studies evaluating pCPS in patients clinically suspected of PE until June 2023. Risk of bias was evaluated using QUADAS-2. Included pCPS were evaluated based on their diagnostic accuracy in: (1) Ruling-out PE (2) Utilization of imaging, and (3) Differentiating between patients needing d-dimer from imaging. Diagnostic test accuracy indices were synthesized using beta-binomial Bayesian methods. Results Forty studies (37,027 patients) were included in the meta-analysis. Three-tier revised Geneva (RG) and three-tier Wells performed similarly in ruling-out PE (negative likelihood ratio (LR-) [95% credible interval (CI)]: 0·39[0·27–0·58] vs 0·34[0·25–0·45]). However, RG performed better in utilization of imaging (LR + : 6·65[3·75–10·56] vs 5·59[3·7–8·37], p < 0.001) and differentiating between patients needing d-dimer vs imaging (diagnostic odds ratio (DOR): 8·03[4·35–14·1] vs. 7·4[4·65–11·84], p < 0.001). The two-tier Wells score underperformed in all aspects (LR-: 0·56[0·45–0·68], LR + : 2·43[1·81–3·07], DOR: 4·41[2·81–6·43]). PERC demonstrated a reliable point estimate for ruling out PE, albeit with a wide CI (LR-: 0·36[0·17–0·78]). Conclusions RG outperforms other pCPS for primary evaluation of suspected PE. While the difference is not large, RG's independence from subjective items supports its recommendation over three-tier Wells. Two-tier Wells underperforms significantly compared to the rest of pCPS. PERC shows considerable promise for minimizing unnecessary D-dimer testing in crowded emergency departments; however, more evidence is needed before its definitive recommendation. Protocol registration PROSPERO (CRD42023464118).